Research Progress of Sirtuin4 in Cancer - Bai, Yibing; Yang, Jiani; Cui, Ying; Yao, Yuanfei; Wu, Feng; Liu, Caiqi; Fan, Xiaona; Zhang, Yanqiao (Frontiers in Oncology, 2021)
Sirtuins (SIRTs) are members of the silent information regulator-2 family. They are a conserved family of nicotinamide adenine dinucleotide-dependent protein lysine deacylases. SIRTS are involved in intricate cellular processes. There are seven subtypes of SIRTs (1–7) in mammals. SIRT4 is located mainly in mitochondria and has various catalytic activities. These enzyme activities give it a diverse range of important biologic functions, such as energy metabolism, oxidative stress, and aging. Cancer is characterized as reprogramming of energy metabolism and redox imbalance, and SIRT4 can affect tumorigenesis. Here, we review the structure, localization, and enzyme activity of SIRT4 and its role in various neoplasms.